MicroRNA-145 Increases the Apoptosis of Activated Hepatic Stellate Cells Induced by TRAIL through NF-κB Signaling Pathway - Yang, Junfa; Liu, Qingxue; Cao, Shiyang; Xu, Tao; Li, Xiaofeng; Zhou, Dandan; Pan, Linxin; Li, Changyao; Huang, Cheng; Meng, Xiaoming; Zhang, Lei; Wang, Xiao (Frontiers in Pharmacology, 2018)
During the liver fibrosis recovery stage TRAIL can effectively induce apoptosis of activated hepatic stellates cells (HSCs). Normal liver tissues are resistant to TRAIL cytotoxicity. Therefore, enhancing the sensitivity of TRAIL-induced apoptosis of HSCs may be useful to treat hepatic fibrogenesis. Here, we demonstrated that miR-145 and TRAIL were down-regulated in both liver fibrosis tissue samples and transforming growth factor-1 (TGF-β1) induced HSCs, concomitant with increased the expression of ZEB2. In addition, we found that mimics-mediated over-expression of miR-145 led to resistance to the ZEB2 expression and up-regulation of the TRAIL-induced apoptosis after treatment of LX-2 cells with TRAIL. Furthermore, ZEB2-siRNA transfected LX-2 cells showed the increased sensitivity to TRAIL-induced apoptosis. Whereas, opposite results were obtained in miR-145-inhibitor group or ZEB2 plasmid group. Moreover, miR-145 regulated ZEB2 gene expression by specifically interacting with the 3′-UTR of ZEB2 mRNA to inhibit the expression of ZEB2. Further studies showed that the over-expression of ZEB2 could inhibit TRAIL-induced apoptosis via inhibiting nuclear factor-κB (NF-κB) signaling pathway in LX-2 cells. Collectively, our data suggest that up-regulation of miR-145 can down-regulate ZEB2 expression, consequently promoting TRAIL-induced apoptosis in LX-2 cells through NF-κB signaling pathway, which facilitates the resolution of liver fibrosis.